Bioaccumulation of mercury in clams (Meretrix lyrata) cultured at the Bach Dang estuary: a recommendation for safe daily dosage consumption of clams in Viet Nam - Sinh, Le Xuan; Huong, Mai (Vietnam Journal of Science and Technology, 2020)
This study assessed the level of mercury (THg) and methylmercury (MeHg) in seawater and clams (Meretrix lyrata) during all four seasons (July 2010 to May 2011) at the Dong Bai intertidal area in the Bach Dang estuary. The results showed that total mercury and methyl mercuryconcentrations of the water were under the allowable limit. Total mercury and methylmercury concentration for clams ranged from 12.5-87.9 ng/g dw and 1.1-24.6 ng/g dw, respectively. The highest bioaccumulation factor (BAF) of Meretrix lyrata was 303.2 for mercury and 165,000 for methylmercury. The recommended safe dosage for daily clam consumption depends on the season. Over a one-year period, mercury contamination in clams harvested in the Bach Dang estuary ranged from 1.4 to 38.1 g/kg bw. It is not recommended to consume too many clams in March or April.